1999
DOI: 10.1128/jcm.37.4.1165-1167.1999
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of JC Virus in Nontumorous Renal Tissue of a Patient with Renal Cancer but without Progressive Multifocal Leukoencephalopathy

Abstract: We performed immunohistochemical staining on the nontumorous renal tissue of 45 patients with renal cancer but without progressive multifocal encephalopathy using JCV-specific antibody. For one patient we found positive staining of the nuclei of the renal collecting ducts. Immunoelectron microscopic examination of the positive cell nuclei revealed electron-dense polyomavirus-like particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…In our cases, the immunohistochemically positive cells with morphological evidence of viral infection were randomly distributed in the renal parenchyma and focally involved renal tubules. These findings are similar to those reported by Aoki et al (32) and Dorries and ter Meulen (33). in surgical samples, but different from those of Randhawa et al (11), who reported the selective infection of re- nal cortical parenchyma by JC virus in a single kidney transplanted patient.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our cases, the immunohistochemically positive cells with morphological evidence of viral infection were randomly distributed in the renal parenchyma and focally involved renal tubules. These findings are similar to those reported by Aoki et al (32) and Dorries and ter Meulen (33). in surgical samples, but different from those of Randhawa et al (11), who reported the selective infection of re- nal cortical parenchyma by JC virus in a single kidney transplanted patient.…”
Section: Discussionsupporting
confidence: 87%
“…In all of these cases, nPCR of the LT region, followed by restriction fragment length polymorphism analysis, revealed the presence of JC virus, whereas BK virus sequences were never found. Like Aoki et al (32) and Dorries and ter Meulen (33), we did not find any inflammatory infiltration around the renal tubules containing JC virus-positive cells or casts. Randhawa et al (11) reported slight interstitial inflammatory infiltration in close proximity to inclusion-bearing cells stained with anti-JC virus VP1 antiserum, but their case was co-infected with BK virus, which may have been the cause of the inflammatory infiltration.…”
Section: Discussionsupporting
confidence: 84%
“…Even though JCV infection has never revealed any histopathological changes in the kidney, viral DNA is commonly detected in the renal cortex and medulla of more than 50% of individuals. 20,54 We used the SNA and MAA lectins to probe 5.0-m-thick kidney sections for the presence of ␣2,6and ␣2,3-linked SA, respectively. Figure 6A shows that the receptor-type SA expression is high in the kidney demonstrated by staining of the renal glomerulus and the surrounding tubules.…”
Section: Expression Of the Jcv Receptor-type Sa In Human Kidney And Lungmentioning
confidence: 99%